Seeing the Combined Effects of Aid Programmes - Burge, Richard; Nadelman, Rachel; McGee, Rosie; Fox, Jonathan; Anderson, Colin (Institute of Development Studies, 2022)
Multiple aid agencies often try to support change in the same places, at the same time, and with similar actors. Surprisingly, their interac tions and combined effects are rarely explored. This Policy Briefing d escribes findings from research conducted on recent aid programmes tha t overlapped in Mozambique, Nigeria, and Pakistan, and from a webinar with UK Foreign, Commonwealth & Development Office (FCDO) advisors and practitioners. The research found three distinct categories of ‘inter action effects’: synergy, parallel play, and disconnect. We explore ho w using an ‘interaction effects’ lens in practice could inform aid age ncy strategies and programming.